2021
DOI: 10.1542/peds.2020-030643
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive Breastfeeding, Child Mortality, and Economic Cost in Sub-Saharan Africa

Abstract: BACKGROUND: Sub-Saharan Africa remains the region with the highest under-5 mortality (U5M) rates globally. Emerging evidence revealed that exclusive breastfeeding (EBF) rates are significantly associated with a decreased risk for child mortality. Our aim with this study is to fill the gap of knowledge regarding the economic impact of EBF practices in relation to U5M in sub-Saharan African countries. METHODS: Data were gathere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
(18 reference statements)
0
17
0
1
Order By: Relevance
“…In India, early termination of breastfeeding, suboptimal level of breastfeeding initiation and exclusive breastfeeding were found to base on urbanicity, higher level of mother education and higher household socioeconomic position [6]. Improvement in EBF prevalence increased per capita total cumulative non-health GDP significantly and decreased under 5-mortality rate, reduction of economic cost found in a meta-analysis of sub-saharan Africa [7]. Nigerian study identified some of the major factors which are the culprits for non-EBF practices and highlighted that the significant factors associated with non-EBF practices were a low rate of maternal education, lesser availability of antenatal care, poor to middle household wealth, and lesser availability and awareness for maternal care after birth.…”
Section: Introductionmentioning
confidence: 95%
“…In India, early termination of breastfeeding, suboptimal level of breastfeeding initiation and exclusive breastfeeding were found to base on urbanicity, higher level of mother education and higher household socioeconomic position [6]. Improvement in EBF prevalence increased per capita total cumulative non-health GDP significantly and decreased under 5-mortality rate, reduction of economic cost found in a meta-analysis of sub-saharan Africa [7]. Nigerian study identified some of the major factors which are the culprits for non-EBF practices and highlighted that the significant factors associated with non-EBF practices were a low rate of maternal education, lesser availability of antenatal care, poor to middle household wealth, and lesser availability and awareness for maternal care after birth.…”
Section: Introductionmentioning
confidence: 95%
“…Malnutrition-related causes of neonatal morbidity, mortality, and impaired child growth coupled with the consequential effects on socio-economic development remains a major public health concern especially in developing countries [1][2][3][4][5][6]. The risk of under five mortality when initiation of breastfeeding is delayed in sub-Saharan Africa (SSA) was estimated to be threefold higher compared to any kind of infant feeding as 55.3% of under-five mortality is attributable to delayed initiation of breastfeeding [1].…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true for babies who are adopted after their biological mother’s death or who are abandoned for any reason. Non-puerperal adoptive breastfeeding can be lifesaving for these adopted infants (Pretorius et al, 2021).…”
Section: Introductionmentioning
confidence: 99%